2014
DOI: 10.1002/apj.1837
|View full text |Cite
|
Sign up to set email alerts
|

Mixing enhancement of a passive microfluidic mixer containing triangle baffles

Abstract: Micromixing plays a significant role in microfluidics. Here a passive mixer with triangle baffles embedded in the main channel was designed, fabricated and characterized. Systematic simulations and experiments have been done with the increase of Reynolds number (Re), ranging from 0.1 to 500. All results confirmed the improvement of mixing within a short distance (<6.4 mm). At common flow rate of microfluidics (Re = 1.0), 'the percentage of mixing' (φ) can be 85.5% by the distance of 6.4 mm, which is 2.48-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…As the global trend is shifting towards microsystem technology development, this vital fluid-mixing process is also in search of mixing the fuel and oxidizer at the micro level. The design of MMs has been broadly examined with the aid of computational fluid dynamics (see previous studies [220][221][222][223][224][225][226][227]. The molecular diffusion process is also involved under certain standardized conditions, though such a mixing strategy is generally quite inefficient due to very low molecular diffusivities.…”
Section: Combustion Technologymentioning
confidence: 99%
“…As the global trend is shifting towards microsystem technology development, this vital fluid-mixing process is also in search of mixing the fuel and oxidizer at the micro level. The design of MMs has been broadly examined with the aid of computational fluid dynamics (see previous studies [220][221][222][223][224][225][226][227]. The molecular diffusion process is also involved under certain standardized conditions, though such a mixing strategy is generally quite inefficient due to very low molecular diffusivities.…”
Section: Combustion Technologymentioning
confidence: 99%
“…Wang et al [19] carried out simulations and experimental investigations on a passive microfluidic mixer containing triangular baffles. Wang et al [19] carried out simulations and experimental investigations on a passive microfluidic mixer containing triangular baffles.…”
Section: Introductionmentioning
confidence: 99%
“…Using baffles and inserting obstacles in the channels is another common approach used previously by researchers in the context of passive mixing. Wang et al [19] carried out simulations and experimental investigations on a passive microfluidic mixer containing triangular baffles. They found that the mixing efficiency of their design was much better than that of a common Y-mixer over a wide range of Re from 0.1-500, and concluded that more groups of the triangular baffles and bigger apical angles lead to better mixing of the solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The role of microfluidic systems is becoming more and more important during the past decades, especially in chemical synthesis and biological diagnosis . Micromixing is one of the most important decisive factors in most of the microfluidic reactions and diagnostic assays . Hence, novel channel designs need to be developed in order to gain excellent mixing effect.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Micromixing is one of the most important decisive factors in most of the microfluidic reactions and diagnostic assays. [10,11] Hence, novel channel designs need to be developed in order to gain excellent mixing effect. There are mainly two broad types of mixers, i.e.…”
Section: Introductionmentioning
confidence: 99%